2022
DOI: 10.37394/23209.2022.19.30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurial Orientation and Service Innovation on Sustainable Competitive Advantage on the Performance of 3, 4 and 5 Star Hotels in Indonesia

Abstract: The purpose of this study was to determine the effect of entrepreneurial orientation and service innovation on sustainable competitive advantage on the performance of 3,4 and 5 star hotels in Indonesia. The researchers took a quantitative approach by measuring the sample variables built from the construct and representing the research population. The unit of analysis in this study is a company engaged in accommodation services (hotels) with 3, 4, and 5 stars spread throughout Indonesia, namely in Bali, West Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…A study on the development of coffee tourism in Campakamulya Village, Bandung, West Java, used PESTLE analysis to assess external factors and identify key elements for strategic planning in rural tourism [11]. Similarly, a study on the performance of [12], [13], and 5-star hotels in Indonesia found that entrepreneurial orientation and service innovation positively affect sustainable business growth and firm performance [14].…”
Section: Introductionmentioning
confidence: 99%
“…A study on the development of coffee tourism in Campakamulya Village, Bandung, West Java, used PESTLE analysis to assess external factors and identify key elements for strategic planning in rural tourism [11]. Similarly, a study on the performance of [12], [13], and 5-star hotels in Indonesia found that entrepreneurial orientation and service innovation positively affect sustainable business growth and firm performance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo concluye que la adopción de tecnologías de la información y la orientación emprendedora de estas organizaciones no tuvieron un efecto positivo sobre el desempeño (Sarya et al, 2023). Por otra parte, un estudio realizado entre restaurantes mexicanos documentó que la orientación al cliente y la innovación en mercadotecnia se relacionaron positiva y significativamente con el desempeño de estas organizaciones (Cerón et al, 2023).…”
unclassified